2020
DOI: 10.1007/s13753-020-00316-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Reduction Through Data Management in the Development, Validation, Calibration, and Operation of a Hurricane Vulnerability Model

Abstract: Catastrophe models estimate risk at the intersection of hazard, exposure, and vulnerability. Each of these areas requires diverse sources of data, which are very often incomplete, inconsistent, or missing altogether. The poor quality of the data is a source of epistemic uncertainty, which affects the vulnerability models as well as the output of the catastrophe models. This article identifies the different sources of epistemic uncertainty in the data, and elaborates on strategies to reduce this uncertainty, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The median estimates exhibit a satisfactory level of agreement with the observed losses, which is consistent with typical outcomes observed in validation exercises for models demonstrating overall good performances (e.g., Amadio et al 2019;Molinari et al, 2020). It should be noted that the model tends to overestimate lower entity damages across all building types (Figure 7), but this discrepancy, rather than being a consequence of any model-related issue, can be primarily attributed to the limitations in the representativeness of claim data, particularly for minor losses, as documented in the literature Molinari et al, 2020;Pinelli et al, 2020). 340 While confirming the performance of INSYDE 2.0 in accurately depicting the overall damage figures of the two events (Dottori et al, 2016;Amadio et al, 2019;Molinari et al, 2020), the results of this analysis also emphasize the advantages of incorporating the treatment of input data uncertainty when presenting the outcomes of a model validation.…”
Section: Analysis On Field Data From Recent Flood Eventssupporting
confidence: 82%
“…The median estimates exhibit a satisfactory level of agreement with the observed losses, which is consistent with typical outcomes observed in validation exercises for models demonstrating overall good performances (e.g., Amadio et al 2019;Molinari et al, 2020). It should be noted that the model tends to overestimate lower entity damages across all building types (Figure 7), but this discrepancy, rather than being a consequence of any model-related issue, can be primarily attributed to the limitations in the representativeness of claim data, particularly for minor losses, as documented in the literature Molinari et al, 2020;Pinelli et al, 2020). 340 While confirming the performance of INSYDE 2.0 in accurately depicting the overall damage figures of the two events (Dottori et al, 2016;Amadio et al, 2019;Molinari et al, 2020), the results of this analysis also emphasize the advantages of incorporating the treatment of input data uncertainty when presenting the outcomes of a model validation.…”
Section: Analysis On Field Data From Recent Flood Eventssupporting
confidence: 82%
“…There are many uncertainties in the process of flood risk assessment. Pinelli et al (2020) found that there is inevitable uncertainty in estimating the value of assets. Koks et al (2019) showed that the economic damage caused by the failure of critical infrastructure might be underestimated.…”
Section: Limitations and Validationmentioning
confidence: 99%
“…The land use data can be easily obtained through remote sensing (RS) interpretation [14], and it is effectively used to extract the spatial distribution of buildings, but it is difficult to establish the relationship between flood loss data and land use types. These problems lead to high uncertainties and disparities in flood loss assessments [19,20]. In this case, we should propose a refined method to evaluate the detailed flood loss of each affected object.…”
Section: Introductionmentioning
confidence: 99%